Women Education Condition in Rajasthan after Independence 1950-2000: Challenges and Obstacles in Women's Education in Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Rajasthan Hindu society has been most conservative of structure as far as the social scenario is concerned. The norms and traditions governing the society were so strict that they not be violated or overstepped by women. There was particular focus on women’s attachment to the social customs and traditions, while shaped their behaviour and guided them at every step. Customs like sati, child marriage etc. was widely normal in the society. Many British officers took an active interest in seeking remedies to cure such ills. As boys go to schools girls replace them in labour besides doing their usual domestic work responsibilities. It is shocking to note that the percentage of girls of 11 to 13 years of age in rural labour force which was 24 percent in 1981 has gone up to 30 percent. They prefer to pick up that amount of expenditure on their boy kin than daughters. Besides, the future cost of educated daughters is considered to be higher as educated girls will be required to be married to better educated boys only, who demand higher dowry. Another obstacle for sending daughters to schools is concern for their virginity. Because schools in rural areas are located at longer distances teachers in these schools are generally males, schools are common for both boys and girls on account of who parents are disinclined to expose their daughters to possible assault of virginity which plays a vital role in removing young girls from schools.